Conjugated Linoleic Acid Isomers Trans‐10, Cis‐12 and Cis‐9, Trans‐11 Prevent Collagen‐Induced Arthritis in a Direct Comparison. Issue 7 (27th September 2018) - Muhlenbeck, Jessica A.; Olson, Jake M.; Hughes, Anna B.; Cook, Mark E.
Abstract: Mixed‐isomer conjugated linoleic acid (CLA) and the individual isomers, trans ‐10, cis ‐12 (CLAt10c12) and cis ‐9, trans ‐11 (CLAc9t11), decrease severity of collagen‐induced arthritis (CA) when consumed after disease onset. Few studies have been conducted exploring the role of CLA in the prevention of autoimmune diseases. These studies suggest that isomer‐specific effects may be occurring; however, a direct comparison of CLAt10c12 and CLAc9t11 has yet to be conducted. A study to compare the ability of CLAt10c12 and CLAc9t11 to prevent CA and assess their effects on early inflammation was performed. DBA/1 mice were fed a semipurified diet containing 6% corn oil (CO), 5.5% CO and 0.5% CLAt10c12, or 5.5% CO and 0.5% CLAc9t11 ( n = 27 per diet) starting three weeks before CA primary immunization. Effects on disease incidence and severity, anticollagen antibodies, plasma and paw cytokines, and hepatic fatty acids were measured. Arthritis incidence was reduced by a minimum of 34% in mice fed either CLA isomer compared to those fed CO diet ( p = 0.06). In mice that did develop arthritis ( n = 9–12 mice per treatment), CLAt10c12 reduced arthritic severity to a greater extent than CLAc9t11 and CO ( p = 0.03). CLA isomer treatment attenuated the increased hepatic arachidonic acid (ARA; 20:4n‐6) observed with arthritis at one‐week postonset ( p = 0.03), while no differences in anticollagen antibodies or cytokines were observed between dietary treatments. These results suggest that CLA isomers may be effective at preventing specific immune‐mediated inflammatory diseases, in part, through modulation of the ARA cascade.